Evaluation of Tehran university of medical sciences dental students\' attitude toward their field of study and future - Ahmad Jafari; Pooria Gharagozloo; Ali Baghalian (Tehran University of Medical Sciences, 2020)
Background and Aims: Interest and satisfaction of students toward their field of study has important role in knowledge promotion, future activities, and also healthcare of country. This study aimed to evaluate the attitude of dental students toward their field of study and also their future career. Materials and Methods: This cross-sectional descriptive study was based on a standardized researcher designed questionnaire in 2018. Demographic data was collected and questions were based on the attitude of students toward their field of study and their future. ANOVA and Backward stepwise regression methods were used for statistical analysis. Significance level was determined at 0.05. Results: In this study 62.2% of responders were female and 37.8% were males. Students chose dentistry under the influence of following matters consecutively: high income, recommendation of people around and self-interest. Girls compared to boys, were significantly influenced more by self-interest and also had more interest compared to boys for working in dentistry (P<0.05). Also, most of students were anxious about the increase in the number of dental students. Conclusion: Students had positive attitude toward their field of study and their future. They were interested in working in this field but factors such as not having enough familiarity toward this field and also an increase in the number of students in recent years created some worries for them.